(3TQYI GdESdGes - (3GdLhZj, EeGe RGOg, Qcf GdESdGe (B- (3EeGe RGOg, eMeO Hf CHj HcQ, (B573 (3gs
(3ChdgG (B:s
(3hHYO agPg YbhO efXheI ef Sff SjO GdYGdejf hSejJg TQYI GdESdGes
(3BNQgG (B:s
(3fGbU GdBNQ, hBNQg(B: (3dg Yedg Edi jhe GdbjGeI hcGfJ aJfI GdbHQ haj GdMOjK Cf CQhGM GdTgOGA hMhGUds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 54s
(3eYLe GdeDdajf(B: 3 / 164s
(3cTa GdXfhf(B: 2 / 1044s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs